"The Reality of the Present and the Challenge of the Future": J. Fagg Foster for the Twenty-First Century. Issue 1 (2nd January 2016) - Wray, L. Randall
Abstract: This paper revisits J. Fagg Foster's early assessment of the relevance of John Maynard Keynes's theory of institutional economics. In his view, neither institutionalists nor most of Keynes's followers really recognized the importance of Keynes's theoretical insights. I examine Foster's views on economic theory, with a particular focus on monetary theory. I apply Foster's approach to what is now called modern money theory, an approach developed by heterodox economists working in the institutionalist and post-Keynesian traditions. I argue that this approach is consistent with Foster's, and it offers a way forward to policy formation for the twenty-first century.